Critical success factors in library reengineering: a case of academic libraries in Kenya. Issue 6 (2nd September 2019) - Musangi, Penninah Syombua; Odero, Damaris; Kwanya, Tom
Abstract : Purpose: Academic libraries are reengineering their services to address the gap brought about by the convergence of physical and virtual information landscape. Despite the reengineering efforts, as many as 70 per cent of the libraries do not achieve the expected results. Certain critical success factors need to be in place for successful implementation. This paper aims to investigate the key success factors to service reengineering in an effort to establish their extent of application in university libraries in Kenya. Design/methodology/approach: A multiple case study approach of six purposively selected private and public university libraries in Kenya based on Webometric ranking as an indicator of reengineering was used. Data were collected through face-to-face interviews with 30 librarians. The qualitative data collected were analyzed through content analysis. Findings: The following key success factors were found to have been considered during reengineering: top management commitment, planning, provision of required resources, appropriate IT infrastructure, presence of skilled and competent staff, value of the library to the university and teamwork. Despite the central role of training, change management program and having a clear vision and objectives, university libraries in Kenya did not pay any attention to them as deserved. The authors conclude that university libraries in Kenya have not optimally achieved the desired reengineering results as a result of overlooking training and change management as critical success factors. The paper recommends that the identified critical success factors should be considered wholly not in isolation. Research limitations/implications: The study was carried out among the top-ranked universities according to the January 2017 Webometric ranking; and therefore the findings may give a general indication of the critical success factors considered by university libraries in Kenya. However, this pre-condition may have locked out other libraries that may have made some recommendable strides in re-engineering their services. Originality/value: This study has practical implications in identifying the critical success factors for library service reengineering to provide insights on the factors to consider as librarians reengineer library services.